2014
DOI: 10.1021/ja502275w
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Hydroamination of 1,3-Dienes Catalyzed by Bis(phosphine)carbodicarbene–Rhodium Complexes

Abstract: A carbodicarbene (CDC)-based pincer ligand scaffold is reported, along with its application to site-selective Rh(I)-catalyzed intermolecular hydroamination of 1,3-dienes with aryl and alkyl amines. To the best of our knowledge, this is the first example of the use of a well-defined CDC complex as an efficient catalyst. Transformations proceed in the presence of 1.0-5.0 mol % Rh complex at 35-120 °C; allylic amines are obtained in up to 97% yield and with >98:2 site selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(65 citation statements)
references
References 49 publications
1
64
0
Order By: Relevance
“…At this juncture, attempts to isolate the free pincer CDC 45 were unsuccessful. The salt 44 could be converted to the square‐planar complex 46 via cyclometalation with [Rh(cod)Cl] 2 in the presence of NaOMe base . The Rh I complex 46 was crystallized as an orange/yellow solid, with the 13 C NMR signal of the CDC carbon(0) appearing as a doublet of triplets at ≈73 ppm.…”
Section: Development and Structural Diversity Of Carbodicarbenesmentioning
confidence: 99%
See 3 more Smart Citations
“…At this juncture, attempts to isolate the free pincer CDC 45 were unsuccessful. The salt 44 could be converted to the square‐planar complex 46 via cyclometalation with [Rh(cod)Cl] 2 in the presence of NaOMe base . The Rh I complex 46 was crystallized as an orange/yellow solid, with the 13 C NMR signal of the CDC carbon(0) appearing as a doublet of triplets at ≈73 ppm.…”
Section: Development and Structural Diversity Of Carbodicarbenesmentioning
confidence: 99%
“…The teams of Meek and Ong are considered pioneers in employing CDCs as supporting ligands in catalysis. Meek and coworkers demonstrated that the pincer CDC Rh I complex 46 efficiently catalyzed intermolecular hydroamination of 1,3‐diene substrates with various aryl and alkyl amines (Scheme ) . For example, complex 46 in the presence of a catalytic amount of AgBF 4 catalyzed the hydroamination of phenyl 1,3‐butadiene ( O1‐a ) with p ‐CF 3 or p ‐methoxy‐substituted anilines ( O2 ) to afford allylic amines ( O4 ) with >98 % γ‐selectivity in excellent yield.…”
Section: Carbodicarbenes In Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Other alkenes that have been activated for hydroamination include those possessing substituents that enable a stepwise pathway. Examples of such alkenes include Michael acceptors, alkenes bearing directing groups, 1214 and alkenes that react to form allyl or benzyl complexes, such as dienes, 1517 allenes, and vinylarenes. 1826 Likewise, strained bicyclic alkenes 27,28 undergo migratory insertion steps more quickly than unstrained alkenes and form alkyl intermediates that do not undergo β-hydrogen elimination to form oxidized products.…”
Section: Introductionmentioning
confidence: 99%